2018
DOI: 10.1167/18.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Placeholder objects shape spatial attention effects before eye movements

Abstract: In the time leading up to a saccade, the saccade target is perceptually enhanced compared to other objects in the visual field. This enhancement is attributed to a shift of spatial attention toward the target. We examined whether the presence of visual objects is critical for the perceptual enhancement at the saccade target to occur. We hypothesized that attention may need an object to focus on in order to be effective. We conducted four experiments using a dual-task design, where participants performed eye mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
3
9
0
Order By: Relevance
“…This demonstrates that visual structures pose the risk of compromising the attention measurement in a non-systematic way. In line with previous work showing the impact of placeholder objects on attentional modulations of visual perception (Taylor et al, 2015; Puntiroli et al, 2018; Szinte et al, 2019), these findings underline the necessity of an unbiased, item-free approach to map perceptual dynamics across the visual field in the absence of object-like structures.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This demonstrates that visual structures pose the risk of compromising the attention measurement in a non-systematic way. In line with previous work showing the impact of placeholder objects on attentional modulations of visual perception (Taylor et al, 2015; Puntiroli et al, 2018; Szinte et al, 2019), these findings underline the necessity of an unbiased, item-free approach to map perceptual dynamics across the visual field in the absence of object-like structures.…”
Section: Resultssupporting
confidence: 89%
“…However, these conventional approaches face a common shortcoming: They all rely on localized test stimuli to determine the deployment of visual attention. The potential problem with this approach is that these stimuli could bias visual perception by structuring the visual field (Taylor, Chan, Bennett, & Pratt, 2015; Puntiroli, Kerzel, & Born, 2018; Szinte, Puntiroli, & Deubel, 2019; Shurygina, Pooresmaeili, & Rolfs, 2021) and may thus affect what they are intended to measure – the spatial distribution of attention. In a paradigm using a typical stimulus configuration as displayed in Figure 1A , attention is likely biased towards the presented stimuli (as compared to locations in between or further in- or outside), since those are the only locations containing potentially task-relevant visual information ( Figure 1B ).…”
Section: Introductionmentioning
confidence: 99%
“…While our findings match those of studies which investigated the allocation of attention with a continuously presented cue 6,13,14,18,20,22,23,30,31 , these studies were all using a structured visual field of visual placeholders. Puntiroli and colleagues 21 is to our knowledge the only study in which the effect of visual placeholders on the presaccadic shift of attention was investigated. They measured the relative performance in discriminating a cross displayed at three possible placeholders, the saccade target and two distractors, either present or absent of the screen in different blocks of trials.…”
Section: Discussionmentioning
confidence: 99%
“…But, do these effects reflect the precision of the spatial deployment of the presaccadic shift of attention or the use of a structured visual scene for their assessment? Puntiroli and colleagues 21 recently tested the influence of a structured visual field composed of several placeholders on the deployment of attention. They observed that the presaccadic shift of attention reduces potential masking effects that flankers can have on the saccade target.…”
Section: Introductionmentioning
confidence: 99%
“…They may act as ''anchors'' that help direct attention to certain locations or regions (Jefferies & Di Lollo, 2015), to objects (Egly, Driver, & Rafal, 1994), or to groups of objects (Dodd & Pratt, 2005). They improve the accuracy of gazed-at locations (Wiese, Zwickel, & Müller, 2013) and generally shape the focus of spatial attention before and during eye movements (Lisi, Cavanagh, & Zorzi, 2015;Puntiroli, Kerzel, & Born, 2018). What appears surprising, however, is the reported differential effect of placeholders on facilitatory and inhibitory attentional modulations.…”
Section: Introductionmentioning
confidence: 99%